Asymmetrical Flow Field-Flow Fractionation Methods for Quantitative Determination and Size Characterization of Thiols and for Mercury Size Speciation Analysis in Organic Matter-Rich Natural Waters - Worms, Isabelle A. M.; Kavanagh, Killian; Moulin, Elodie; Regier, Nicole; Slaveykova, Vera I. (Frontiers in Chemistry, 2022)
Asymmetrical flow field-flow fractionation (AF4) efficiently separates various macromolecules and nano-components of natural water according to their hydrodynamic sizes. The online coupling of AF4 to fluorescence (Fluo), UV absorbance (UV) detectors (-D) and inductively coupled plasmas mass spectrometry (ICP-MS) provides a multi-dimensional information. This makes it a powerful tool to characterize and quantify the size distributions of organic and inorganic nano-sized components and their interaction with trace metals. In this study we developed a method combining thiol-labeling by monobromo-(trimethylammonio)-bimane bromide (qBBr) with AF4−FluoD to determine the size distribution and the quantities of thiols of macromolecular dissolved organic matter (DOM) present in highly colored DOM-rich water sampled from Shuya River and Lake Onego, Russia. We found that qBBr-labeled components of DOM (qB−DOM) were of humic type, characterized by low hydrodynamic size (dh < 2 nm), and have concentrations < 0.3 M. After enrichment with mercury, the complexes formed between nano-sized components and Hg were analyzed by AF4−ICP-MS. The elution profile of Hg followed the distribution of UV-absorbing components of DOM, characterized by slightly higher sizes than qB−DOM. Only a small proportion of Hg was associated to larger-size components containing Fe and Mn, probably inorganic oxides which were identified in most of the samples from river to lake. The size distribution of Hg−DOM complexes was enlarged when the concentration of added Hg increased (from 10 to 100 nM). This was explained by the presence of small iron oxides, overlapping Hg−DOM size distribution, on which Hg bind to a small proportion. In addition to provide information on the dispersion of macromolecular thiols in colored DOM-rich natural water, our study also illustrated the potential of the AF4−FluoD−UVD−ICP-MS to trace or quantify dynamic changes while Hg bind to natural nano-colloidal components of surface water.